RNAi reveals proteins for metabolism and protein processing associated with Langat virus infection in Ixodes scapularis (black-legged tick) ISE6 cells. Issue 1 (December 2017) - Grabowski, Jeffrey; Gulia-Nuss, Monika; Kuhn, Richard; Hill, Catherine
Abstract Background Tick-borne flaviviruses (TBFs) cause thousands of human cases of encephalitis worldwide each year, with some TBF infections progressing to hemorrhagic fever. TBFs are of medical and veterinary importance and strategies to reduce flavivirus transmission by the tick vector may have significant application. Analyses of the proteome of ISE6 cells derived from the black legged tick, Ixodes scapularis infected with the TBF, Langat virus (LGTV), have provided insights into proteins and cellular processes involved with LGTV infection. Methods RNA interference (RNAi)-induced knockdown of transcripts was used to investigate the role of ten tick proteins in the LGTV infection cycle in ISE6 cells. LGTV-infected cells were separately transfected with dsRNA corresponding to each gene of interest and the effect on LGTV genome replication and release of infectious virus was assessed by RT-qPCR and plaque assays, respectively. Results RNAi-induced knockdown of transcripts for two enzymes that likely function in amino acid, carbohydrate, lipid, terpenoid/polykeytide and vitamin metabolism, and a transcript for one protein of unknown function were associated with decreased replication of the LGTV genome and release of infectious virus from cells. The knockdown of transcripts for five enzymes predicted to function in metabolism, a protein likely associated with folding, sorting and degradation, and a protein of unknown function was associated with a decrease only in the amount of infectious LGTV released from cells. Conclusions These data suggest tick proteins potentially associated with metabolism and protein processing may be involved in LGTV infection of ISE6 cells. Our study provides information to begin to elucidate the function of these proteins and identify targets for the development of new interventions aimed at controlling the transmission of TBFs.